2017
DOI: 10.3897/natureconservation.22.19809
|View full text |Cite
|
Sign up to set email alerts
|

Conservation biology of the last Italian population of Cistus laurifolius (Cistaceae): demographic structure, reproductive success and population genetics

Abstract: Isolated populations are usually subject to low fitness and reduced genetic diversity, both of which may negatively affect their survival and adaptive potential. Hence, these issues cannot be neglected when planning conservation actions for isolated populations. The Italian population of Cistus laurifolius subsp. laurifolius is extremely isolated. Furthermore, it is affected by fragmentation, being constituted by a single larger subpopulation, surrounded by three much smaller subpopulations, a few hundred metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…Allele peaks were detected within the size range reported in the literature [28,29]. The most diverse loci were cislau1-1 followed by cislau12-1, presenting 10 and 8 alleles, respectively, which were findings that were comparable to the results of Astuti et al [28] and Bertolasi et al [29].…”
Section: Genetic Population Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…Allele peaks were detected within the size range reported in the literature [28,29]. The most diverse loci were cislau1-1 followed by cislau12-1, presenting 10 and 8 alleles, respectively, which were findings that were comparable to the results of Astuti et al [28] and Bertolasi et al [29].…”
Section: Genetic Population Analysissupporting
confidence: 87%
“…Five microsatellite loci developed by Astuti et al [28] for Cistus laurifolius L. and had been successfully tested for their ability to amplify C. albidus DNA samples according to Bertolasi et al [29] were used to analyze the genetic population structure of the three C. creticus L. populations. The sequences and traits of the SSR markers are presented in Table 1.…”
Section: Microsatellite Locimentioning
confidence: 99%
“…The patterns of genetic variation found with SSR analysis are best explained by ecological histories and not by the present habitat in this genus as well (Furches et al 2013). Last, in a study very similar in scope to our work, it was found that the only remaining Italian population of Cistus laurifolius (laurel-leaved rock rose) derives its low genetic variation and high inbreeding from its narrow ecological requirements and recent habitat fragmentation (Astuti et al 2017).…”
Section: Genetic Variability and Differentiationsupporting
confidence: 76%
“…Last, in a study very similar in scope to our work, it was found that the only remaining Italian population of Cistus laurifolius (laurel‐leaved rock rose) derives its low genetic variation and high inbreeding from its narrow ecological requirements and recent habitat fragmentation (Astuti et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…We obtained the anthers from the 673 buds instead from open flowers to ensure that anthers had not dehisced and pollen had not been dispersed. For effective pollen release, anthers were pricked with a sterile needle, then sonicated for 40 min at 42 kHz using a Cole-Parmer 8890 Ultrasonic Bath (Cole-Parmer, Vernon Hills, IL, USA; Astuti et al, 2017). Then, we counted the pollen grains in 500-μL subsamples using a particle counter (Coulter Multisizer 3, Beckman Coulter, Fullerton, CA, USA).…”
Section: Data Collectionmentioning
confidence: 99%